2019
DOI: 10.1016/j.cub.2019.04.069
|View full text |Cite
|
Sign up to set email alerts
|

A SNP in a Steroidogenic Enzyme Is Associated with Phenotypic Sex in Seriola Fishes

Abstract: Highlights d A trans-species SNP in a steroidogenic Hsd17b1 determines sex in genus Seriola d The Z-linked allele of HSD17B1 attenuates E1 to E2 conversion activity d The data support a long-standing hypothesis on steroidinduced sex determination

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 82 publications
(94 reference statements)
5
92
0
Order By: Relevance
“…In general, it is thought that the sex of plants as well as animals is controlled by heteromorphic sex chromosomes, such as XY or ZW systems, or by sex-linked genome regions in which recombination is highly suppressed at the kb- or Mb-scale (Charlesworth, 2016). It was also recently reported that a single gene or a single base mutation in homomorphic chromosomes is involved in sex determination in amphibia and Seriola fish (Koyama et al, 2019; Miura, 2017). It therefore remains possible that sex determination could be controlled by a single gene in some plants, one of which may be fig.…”
Section: Discussionmentioning
confidence: 94%
“…In general, it is thought that the sex of plants as well as animals is controlled by heteromorphic sex chromosomes, such as XY or ZW systems, or by sex-linked genome regions in which recombination is highly suppressed at the kb- or Mb-scale (Charlesworth, 2016). It was also recently reported that a single gene or a single base mutation in homomorphic chromosomes is involved in sex determination in amphibia and Seriola fish (Koyama et al, 2019; Miura, 2017). It therefore remains possible that sex determination could be controlled by a single gene in some plants, one of which may be fig.…”
Section: Discussionmentioning
confidence: 94%
“…Our simulations (Figure 8) provide insight into how to distinguish the mode of selection at a linked locus. Shortly after turnover, if divergence between male and female haplotypes is restricted in a very narrow region around the sex-determining locus, it may be likely that the sex-determining allele has become established with no help from linked selection (i.e., Myosho et al (2012); Kamiya et al (2012); Koyama et al (2019)). On the other hand, a highly diverged region spreads surrounding the sex-determining locus, the sex-determining allele has become established together with a linked allele at a sexually antagonistic locus, or sexually antagonistic loci arose after the establishment of the sex-determining locus.…”
Section: Discussionmentioning
confidence: 99%
“…MD simulations have been applied to many phenomena of biological polymers (e.g. protein-protein interaction) [19][20][21][22][23][24] as well as chemical reactions [25][26][27]. In these studies, detection of structural change is essential.…”
Section: Multiplicity In Rbps In Living Cellsmentioning
confidence: 99%